Odpowiedzi

2010-02-03T20:55:17+01:00
A)2x-7-[5x² -3x-(2-4x+x ²)]= 2x-7-[5x²-3x-2+4x-x²]=
= 2x-7- 5x²+3x+2-4x+x²=-4x²+ x -5
b)3-x² -[2-2x²-(3x²-2x-1)] =
3- x²- (2-2x²-3x²+2x+1)= 3-x²-2+2x²+3x²-2x-1= 4x²-2x+2
c)4x+3-[x-3x²-(6-3x-x²)]= 4x+2-(x-3x²-6+3x+x²)= 4x+2-x+3x²+6-3x-x²=
2x²+8
d)3x²-5x-[x-3x-(2+4x-x²)] = 3x² - 5x-(x-3x-2-4x+x²)= 3x²-5x-x+3x+2+4x-x²= 2x²+2x+2
14 4 14
2010-02-03T21:04:07+01:00
A) 2x-7-[5x2 -3x - (2-4x +x2)] = 2x-7-[5x2-3x-2-2x-x2]= 2x - 7- 5x2 + 3x +2 -2x +x2 = 3x- 4x2 -5
b) 3- x2 - [ 2- 2x2 - ( 3x2 -2x - 1)] = 3- x2 -[2 - 2x2 - 3x2 + 2x +1]= 3- x2 - 2 + 2x2 + 3x2 - 2x -1 = 4x2 - 2x
c)4x +3 -[ x - 3x2 - (6- 3x - x2)]= 4x + 3- [ x- 3x2 - 6 +3x + x2]= 4x +3 - x + 3x2 +6 - 3x - x2 = 2x2 +9
d) 3x2 -5x - [ x - 3x -2 - 4x +x2 ] = 3x2 - 5x - x + 3x +2 +4x -x2= 2x2 +x +2
8 2 8